Management of Coronary Artery Disease in Patients With Descending Thoracic Aortic Aneurysms. Issue 9 (30th July 2015) - Rajbanshi, Bijoy G.; Charilaou, Paris; Ziganshin, Bulat A.; Rajakaruna, Chanaka; Maryann, Tranquilli; Elefteriades, John A.
Abstract Background The combination of descending aortic aneurysm (DAA) with concomitant coronary artery disease (CAD) is associated with increased morbidity and mortality. We review the surgical management for patients with this combined disease. Methods From January 2000 to January 2014, we performed 268 elective surgeries on the descending or thoracoabdominal aorta. Sixty‐six patients (24.7%) had significant CAD. Indications for aortic intervention included thoracoabdominal aortic aneurysm (TAAA) in 28 (42.4%), DAA in 36 (54.5%), and coarctation and ulcer in one each. Fifty‐two (78.8%) patients had prior CAD, with remote coronary intervention in 32 (48.5%). Results Sixteen (24.2%) patients required coronary intervention prior to aortic surgery, percutaneous coronary intervention in three and coronary artery bypass grafting (CABG) in 13 (six off‐pump). We used the right internal thoracic artery (ITA) because of vulnerability of the left ITA during DAA clamping; the left ITA as a free graft or in situ when disease was distant to the left subclavian artery; and off‐pump CABG to avoid manipulation and embolization. Mean duration between coronary intervention and aortic surgery was 37.2 days. There was no mortality or major adverse cardiac events (MACE) following coronary intervention or during interim to aortic surgery. There were two (3%) cardiac mortalities following DAA/TAAA repair. Conclusion CAD is common among patients with DAA/TAAA. We recommend aggressive evaluation and prior treatment of CAD to minimize perioperative MACE. doi: 10.1111/jocs.12596 (J Card Surg 2015;30:701–706)